A literature review of the secondary school experiences of trans youth - McBride, Ruari-Santiago (Journal of LGBT youth, 2021)
In this article I review 83 empirical studies that provide insight into the secondary school experiences of trans youth. The studies show that while some trans youth have affirming experiences, the majority are exposed to institutionalized cisnormativity that makes them vulnerable to macroaggressions, microaggressions and violence within school settings. Trans youth's exposure to institutionalized cisnormativity was found to intersect with multiple vectors of social power, which subject some trans youth to multiple forms of disadvantage, while affording others degrees of privilege. In conclusion, the findings show that trans youth's educational experiences reflect broader structural inequalities yet defy essentialising explanations.